Pholiotina sphagnicola sp. nov. (Bolbitiaceae, Agaricales) from Mongolia - Burenbaatar, G.; Song, Han-Bing; Bau, Tolgor (Phytotaxa, 2024)
A new species Pholiotina sphagnicola sp. nov., was discovered in Mongolia. Its identification was based on phylogenetic analyses of combined nuclear ribosomal DNA internal transcribed spacer region (ITS), nuclear ribosomal DNA 28S subunit (nrLSU), and translation elongation factor 1-alpha (tef1-α), as well as the morphological analyses. The species is characterized by a pileus ranging from hemispherical to convex, with indistinct striae on the margin. The ring is located above the stipe, and the upper sides crenulate-striate. Basidia, which resemble rabbit ears, are 2(1)-spored and have sterigmata ranging from 3 to 13 μm in length. Cheilocystidia are lageniform with a long neck and lanceolate shape; some may exhibit slight swelling at the apex.